An Approach Toward Numerical Investigation of the Mechanical Behavior of Ceramic Foams during Metal Melt Filtration Processes1 . Issue 9 (25th April 2017) - Abendroth, Martin; Werzner, Eric; Settgast, Christoph; Ray, Subhashis
Abstract : This article demonstrates an approach for the numerical modeling of open cell ceramic foams, in order to investigate the thermo‐mechanical behavior during metal melt filtration processes. The described methods include the creation of the geometric models, the fluid‐dynamic simulations of the melt flow using the lattice boltzmann method, and finite element simulations of the ceramic foam under general loads. The paper mainly focuses on the representative geometry generation process, such that the modeled geometry replicates the real foam as far as possible, since high quality models are essential for the quantitative analyses to be reliable. The present parametric studies demonstrate the manner, in which the foam properties may be influenced by changing the geometric and the topological properties, in order to improve the behavior during filtration processes. Abstract : This article describes a numerical modeling approach to investigate the thermomechanical behavior of ceramic foams during metal melt filtration processes. The described methods cover the creation of the geometric models, the fluiddynamic simulations of the melt flow using the lattice boltzmann method, and subsequent finite element simulations.